MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN BULAT MELALUI MEDIA KOREK API BAGI ANAK TUNARUNGU - Kalisni - Kalisni (Jurnal Penelitian Pendidikan Khusus, 2013)
Integer Addition Upgrading Through Media Match For Deaf Children (Action Research in the Classroom IV SLB Tanjungpinang Affairs), Department of Education Thesis Extraordinary Faculty of Education State University of Padang. The research was motivated by the apparent problems in the field is the three deaf children in special schools D.IV class Tanjungpinang State who have difficulty in understanding the concept of summation of integers. This is evident from early childhood skills in doing operations that AP, BK, IF, S, IM, GG, NK, and CM had trouble on a number of questions given to the eighth child is not able to answer with benar.Penelitian aims to improve deaf children in the concept of integer summation media matches. Media lighter stick is a medium that serves to facilitate understanding of operational count because the integers are positive and negative numbers.The research methodology is that researchers use action research (Classroom Action Research) conducted a collaborator with colleagues. The researcher acted as executive activities while peers act as observers on duty to observe and write reports observations during the activity. Subjects were eight children with hearing impairment IVdi SLB class Tanjungpinang Affairs.Results of research conducted padaa first cycle has seen an increase in children in identifying symbol (+), (-), and arithmetic operations on integers, AP, BK, IF, S, IM, GG, NK, and CM capable of working on the given problem although there are still errors. In the second cycle, the eighth child already understands the concept of positive integers and negative integers as well as the meeting of two symbols of operational processes so that existing problems can be solved properly. The conclusions that can be taken after the study that using matchsticks media can enhance the ability of children with hearing impairment in calculating the sum of integers. From the results obtained, to improve integer addition can be used match stick media.